Hubungan Kepatuhan Hemodialisis Dan Dukungan Sosial Terhadap Kejadian Rawat Inap Ulang Pasien Hemodialisis - Sinta Wijayanti (Jurnal Kesehatan Panca Bhakti Lampung, 2019)
Rehospitalization of HD patients has a negative effect on the patient and family which can improve the patient's emotional and family improve the quality of life of the patient. The purpose of this study was to study the relationship between hemodialysis consent and social support for the incidence of rehospitalization for hemodialysis patients. The study design used a cross sectional design with 111 samples of hemodialysis patients with consecutive sampling technique. The instrument used is the HD compliance instrument with using 1 item question regarding hemodialysis and ENRICHD Social Support Instrument (ESSI). Data were processed using computer software programs and performed bivariate analysis using Mann Whitney. The analysis showed a significant relationship between hemodialysis consent (p-value = 0.032) and social support (p-value = 0.0.34). The recommendations of this study are expected nurses to increase educational assistance to patients and families regarding consent to attend hemodialysis.